Sex-Specific Spatiotemporal Variation and Carry-Over Effects in a Migratory Alpine Songbird - de Zwaan, Devin R.; Wilson, Scott; Gow, Elizabeth A.; Martin, Kathy (Frontiers in Ecology and Evolution, 2019)
For migratory animals, events at one stage of the annual cycle can produce constraints or benefits that carry over to subsequent stages. Differing life-history strategies among individuals can influence the expression of these carry-over effects, leading to pronounced within-population variation in migration. For example, reproductive roles can drive spatiotemporal segregation during the non-breeding season and promote sex-specific carry-over effects, such as reproductive effort affecting autumn migration behaviour. For an alpine breeding population of horned larks Eremophila alpestris in northern British Columbia, Canada, we addressed sex-specific variation in migration behaviour and carry-over effects during both autumn and spring migration using light-level geolocators. Males spent more time farther north and arrived an average of 6 days earlier at the breeding site in spring. Females delayed autumn departure following greater reproductive effort, in turn demonstrating flexible migration behaviour by increasing migration speed and decreasing stopover use. Males maintained autumn migration behaviour regardless of reproductive effort or departure date. Finally, both sexes used staging areas in spring (average stopover = 41 days), with consequences for breeding success. Individuals that used staging areas during spring migration exhibited greater nest success and produced 1.8 more fledglings on average than those that migrated directly from their winter site. Consistent use of staging areas may allow individuals to monitor environmental conditions and optimize their breeding arrival date to acquire high-quality territories while avoiding the cost of arriving too early in a harsh alpine habitat. Overall, our results indicate: (1) sex-specific flexibility in migration strategies that carry-over to and from the reproductive period, and (2) spring staging areas may be a critical component of the annual life-cycle for alpine breeding larks. These behaviours may be particularly important for alpine and arctic birds because the stochastic nature of their breeding habitat likely selects for flexible responses to prevailing conditions.